Experimental Practice. Architecture as a Shared Field of an Exploratory Rethink (EAAE Joint Publishings, 2026)
Experimental practice – ExP, a new master course in architecture at NTNU, Norway, starts with the premise that architectural design knowledge is not made from static, unvarying facts. It is not a commodity one can purchase and therefore own it in its primary, unchangeable form. On the contrary, it is owned only when experienced through practices that are experimental and as such open to infinite processes of enquiry and critical thinking; through letting the knowns shift and adapt to everchanging circumstances. ExP tackles and frames its concerns with its course of action, shifts in protocols, experimental methods, and evolving strategies. That is, with an experimental set of actions tested out through the shared design experience and exchanges in real-time/space with student/teacher team members.